2017
DOI: 10.18632/oncotarget.23622
|View full text |Cite
|
Sign up to set email alerts
|

Senescence and cell death in chronic liver injury: roles and mechanisms underlying hepatocarcinogenesis

Abstract: Chronic liver injury (CLI) is a complex pathological process typically characterized by progressive destruction and regeneration of liver parenchymal cells due to diverse risk factors such as alcohol abuse, drug toxicity, viral infection, and genetic metabolic disorders. When the damage to hepatocytes is mild, the liver can regenerate itself and restore to the normal state; when the damage is irreparable, hepatocytes would undergo senescence or various forms of death including apoptosis, necrosis and necroptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…Necrosis is one of the prominent features in acute liver injury 115. Death of necrotic cells is also a distinct feature of hepatic ischemia/reperfusion injury 86.…”
Section: The Outcomes Of Liver Cell Caused By Mnpsmentioning
confidence: 99%
“…Necrosis is one of the prominent features in acute liver injury 115. Death of necrotic cells is also a distinct feature of hepatic ischemia/reperfusion injury 86.…”
Section: The Outcomes Of Liver Cell Caused By Mnpsmentioning
confidence: 99%
“…The liver can repair and regenerate normally if the damage is mild. But when the degree of damage to the liver is severe, hepatocytes lose regenerative capacity, and undergo necrosis, apoptosis or senescence[11,77].…”
Section: Senescence In the Livermentioning
confidence: 99%
“…After confirming the potential anti-CLI effect of QDD, we try to focus on the effects and mechanisms of DQQ against apoptosis. Apoptosis is one of the important causes of liver cell damage, and it is known that endotoxin is the second blow to CLI and induces chronic liver disease progression via gut-liver axis [ 36 , 37 ] and directly damage liver cells and induce hepatocyte apoptosis [ 38 , 39 ]. Preclinical evidence showed that LA reduced liver injury and decreased oxidative stress response, excessive inflammatory response, and fibrotic progression via downregulating endotoxin levels [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%